The impact of China–Africa trade on the productivity of African firms: evidence from Ghana - Hou, J; Fu, X; Mohnen, P (Springer, 2021)
Using firm- and industry-level panel data, this study investigates the impact of the Ghana–China trade on labour productivity of Ghanaian manufacturing firms and compares it to the impact induced by the trade of Ghana with the OECD. The main findings suggest that the productivity effect in Ghanaian manufacturing firms triggered by engaging in international trade activities is contingent upon the industrial competitive advantage and the trading partners. The empirical results show that trading with China creates greater potentials for Ghanaian manufacturing firms to raise productivity in comparison to trading with OECD countries. Higher intensities of imports from China stimulate productivity gains while more exports to China only enhance productivity in industries in which Ghana has a comparative advantage.